Increasing the capacity of souvenir producers in Dumai City through legal socialization - Evi Deliana; Maria Maya Lestari; Zulfikar Jayakusuma (Community Empowerment, 2022)
Riau Province's Dumai City is a popular tourist destination. Since the opening of the Permai (Pekanbaru-Dumai) toll road connecting Pekanbaru City and Dumai City in less than two hours, Dumai has grown in popularity among travelers. The impact of the short journey, one of which is increased mobility among those who travel to Dumai City. Dumai City's souvenir businesses have benefited as a result of this. As a consequence, familiarity with existing provisions is required, particularly in relation to consumer rights to consume food. Several consumer protections provisions have been issued by the government, including Law No. 8 of 1999 and BPOM Regulation No. 31 of 2018. As a result, the purpose of this program is to inform MSME actors about relevant legal provisions. In the field of law, counseling or socialization is used as a method. The socialization was done in collaboration with the City of Dumai's Office of Industry, Cooperatives, and Small and Medium Enterprises. Souvenir makers gain legal knowledge as a result of this socialization, and they are expected to be able to apply that knowledge in their products.